KONSTRUKSI RUANG KOTA POSKOLONIAL DAN RESPONS SPASIAL DALAM NOVEL THE KITE RUNNER KARYA KHALED HOSSEINI - Shabrina An Adzhani (POETIKA, 2014)
; "> In the time of war, people usually migrate from troubled places to the safe and sound cities, promising a better life.However, the position of cities as a promising space is questionable. It is due to the close relation between city utopia andcolonial city. In fact, there are indications of colonial continuation through industrialization which ends up to domination inmany aspects; economy, social, and cultural. One of postcolonial novels written by a diaspora writer, Khaled Hosseini, takesup a theme of migration from a city (Kabul) in a troubled country, Afghanistan, to a city (Fremont) in a more stable country,America. Sara Upstone’s method of reading on spatial politics in postcolonial novels is used here to read how Fremont isconstructed in the novel and the spatial respond occurred. The analysis showed that Khaled Hosseini’s construction uponFremont is that utopia is denied from the beginning of the novel. Fremont becomes oppressive space and yet, it offers possibilitiesfor spatial responds such as displacement and carnivalisation to occur. These are strategies used by those who are subjected tooppression in the city space.Keywords: City space, postcolonial, spatial respond.